Study on UAV Performance using eCalc Software - Shahrulnizam, Mohammad; Mohd Saleh, Siti Juita Mastura (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Address the need for a longer flight duration on hover state for the hexacopter UAV. The main parameters involved were selected and configurations were developed. The configurations will be tested and analyzed using an open-source web calculator for UAV called eCalc. The relationship of propeller size is inversely proportional to the motor rating. The best configuration for the longest flight time was determined and all configurations can be used as models for future experiments.